1794 Md. Laws 246 - (:unkn) unknown (My University, 1794)
That if any member of society shall suffer any damage by storing gunpowder in town, or breaming ships or other vessels at the wharfs, occasioned by the act, assent or direction, of such member, the insurance of such member so suffering damage, shall thereupon become void.
Keywords: GUNPOWDER - STORAGE